Learning management system (LMS) in English as a foreign language learning: A systematic review - Sylvia Sylvia (Edumaspul: Jurnal Pendidikan, 2025)
The integration of Learning Management Systems (LMSs) has transformed English as a Foreign Language (EFL) pedagogy by extending learning beyond classroom boundaries and supporting synchronous as well as asynchronous interactions. Although widely adopted, research on LMS use in EFL remains fragmented, producing varied findings across platforms, skills, and contexts. This study conducts a systematic literature review of empirical research published between 2020 and 2025 in Scopus, Copernicus, and Google Scholar databases. Six thematic areas were analyzed: pedagogical applications, emerging developments, empirical findings, research gaps, theoretical and practical implications, and directions for future inquiry. Findings demonstrate that platforms such as Moodle and MyELT enhance learner proficiency, motivation, and autonomy, especially when used with collaborative and learner-centered tasks. Video conference-supported LMSs provide authentic communicative opportunities, while localized systems such as E-Belajar illustrate context-sensitive adaptation. Nevertheless, challenges persist, including limited digital literacy, infrastructural inequalities, and insufficient institutional support. Emerging developments such as gamification, hybridized LMS ecosystems, mobile learning integration, and AI-driven feedback highlight the shift toward more adaptive and sustainable digital learning models. Theoretically, the review underscores sociocultural and constructivist perspectives by framing LMSs as mediators of interaction, collaboration, and autonomy. Practically, it stresses the importance of teacher training, institutional readiness, and policy alignment to optimize implementation. Future research should pursue longitudinal, comparative, and skill-focused investigations that leverage advanced LMS affordances to inform evidence-based pedagogical innovation in EFL education.